Metode Abû Dâwud dalam Menulis al-Sunan - Ma'sum, Ma'sum (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2011)
In this paper the author will reveal one of the prominent figures who have long been through the mill of hadith more over the quality of his knowledge in this field does not need to worry about, Abû Dâwud made a large contribution which includes hadith of the prophet in the his book. This study on the book of hadith methodology writing is owned by Abû Dâwud hadith have found some result of hadîth da‘îf that contained therein. the indication of hadîth da‘îf loading (also mawdû‘ according to Ibn al-Jawzî version) in the Sunan Abî Dâwud does not reduce the degree of grandeur this al-Sunan. It can be seen on his prudence take a hadith and judging what source the hadith comes from objectively, the existence of hadîth da‘îf in al-Sunan is not based in his negligence and careless, but there is the element of intent. This is because he hold on the rule, it is better to use hadîth da‘îf the one person’s opinion.